Gambaran Kejadian Mortalitas Bayi Usia 0-11 Bulan di RSUD Kabupaten Kediri pada Triwulan I-III Tahun 2024 - Rosa Aulia Sari; Krisnita Dwi Jayanti; Andra Dwitama Hidayat; Ayu Pangestuti; Reni Triyaningtyas (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Background: The importance of hospitals in addressing maternal and infant health issues, particularly in reducing the Infant Mortality Rate (IMR). Objective: To describe the incidence of mortality in infants aged 0-11 months at RSUD Kabupaten Kediri during the first to third quarters of 2024. Method: A descriptive study with a retrospective approach to 50 medical records of infant patients. Results: From 1,908 inpatient visits, there were 50 infant deaths. The characteristics of the deceased infants included a birth weight of 1,500-2,500 grams (46%), an age of 0-6 days (52%), a majority being male (56%), and originating from Pare District (27%). The leading diagnosis for mortality was Low Birth Weight (LBW) (36%), with the majority of mothers aged 20-35 years (74%). The IMR at RSUD Kabupaten Kediri during this period was 27 per 1,000 live births. Conclusion and Recommendations: In the first to third quarters of 2024, RSUD Kabupaten Kediri recorded 1,858 live births and 50 infant deaths aged 0-11 months, with an infant mortality rate of 27 per 1,000 live births, predominantly among infants with low birth weight, with the highest mortality occurring at 0-6 days of age, and most cases originating from Pare District. There is a need for monitoring high-risk infants, particularly those with LBW and male infants, as well as education for high-risk pregnant women during pregnancy, and routine calculation of infant mortality rates every quarter as a basis for decision-making.